KOMPLEKSITAS AUDIT DAN FAKTOR LAIN: APAKAH MEMENGARUHI AUDIT REPORT LAG - Irene, Irene; Tjahjono, Rudi Setiadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study is to provide empirical evidence regarding the effect of audit complexity, ownership concentration, profitability, solvency, liquidity, audit committee, public accounting firm size, company size, and company age on audit report lag. Audit report lag can be minimized by knowing the factors that affect the audit report lag in companies in Indonesia.This study uses secondary data which is the financial statement data of non-financial companies for the period 2015 to 2019 which are listed on the Indonesia Stock Exchange (IDX). The selected sample in this study has been determined by the criterias using the purposive sampling method. The sample selection of 142 companies was tested using multiple regression analysis. The results of this study indicate that solvency, liquidity, audit committee, size of public accounting firm, and company age have no effect on audit report lag. The results of this study differ from the ownership concentration, profitability, and company size which have a negative effect on the audit report lag. On the other hand, audit complexity has a positive effect on audit report lag.